2022
DOI: 10.3390/ijerph19127286
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Environment: Teacher Experiences during the COVID-19 Pandemic in Ghana

Abstract: Background: In Ghana, the COVID-19 pandemic led to the government’s decision to shut down schools for nearly nine months. This study explores the experiences of preschool teachers in Ghana during the COVID-19 pandemic. Methods: The study was carried out using the Qualitative Description approach and aspects of Albert Bandura’s Social Learning Theory. Twenty-five teachers agreed to carry out face-to-face interviews with the researchers. An audio recorder device was used to record the interviews, with each inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…Teachers continue to seek the best coping strategies for themselves and their students. According to the research by Obeng et al (2022) and Zyna Bartkowiak (2022), teachers experience stress and anxiety due to worries about the safety of their students against the dangers of COVID-19, thereby promoting children to engage in healthy practices. However, this research showed that the stress levels of teachers are concerning for their health as well as for the continuity of education.…”
Section: Coping Strategiesmentioning
confidence: 99%
“…Teachers continue to seek the best coping strategies for themselves and their students. According to the research by Obeng et al (2022) and Zyna Bartkowiak (2022), teachers experience stress and anxiety due to worries about the safety of their students against the dangers of COVID-19, thereby promoting children to engage in healthy practices. However, this research showed that the stress levels of teachers are concerning for their health as well as for the continuity of education.…”
Section: Coping Strategiesmentioning
confidence: 99%